Development possibilities of Environmental Engineering Education – SWOT analysis - Nagy, Georgina; Utasi, Anett; Kurdi, Róbert (International Journal of Engineering and Management Sciences, 2019)
Nowadays we are struggling with many environmental issues that require up-to-date environmental specialists. Amongst the causes of environmental problems, long-standing industrial companies are dominant, for which, on the one hand, the assessment and elimination of existing environmental damage and prevention can be the goal. Universities would be able to provide the necessary knowledge and skills with appropriate educational and research programs. In the research we carried out a comprehensive study of environmental engineering education programs of Hungarian higher education institutions. We analysed the strengths, weaknesses, opportunities and threats of the various educational programs. In addition, on the basis of the analysis we made suggestions on the possible directions of the development of the environmental engineering training.